University Intelligentsia in the Making of Maps: Post-university Networks and Political Change in Slovenia and Poland - Sunandan Roy Chowdhury (Universidad de Navarra, 2018)
The present paper is a result of research done in Slovenia and Poland while the author was a fellow of the Open Society Institute, Budapest between March 2002 and March 2003. The paper looks into the role of a section of university educated intelligentsia in the making of independent Slovenia out of communist Yugoslavia and in the transition of Poland from a one-party communist rule to a multi-party democracy.